Addressing data deficiency in CAADP’s poverty reduction commitment - Ulimwengu, John M.; Tefera, Wondwosen (AKEDEMIYA2063, 2025)
This policy brief examines Africa’s data reporting performance on the commitment to halve poverty under the fourth CAADP Biennial Review (BR) of the Malabo Declaration. Data availability is central to tracking progress, yet approximately 40 percent of the required data was missing at the continental level, with significant disparities across regions, indicators, and countries. Central Africa exhibited the highest rate of missing data, while Western Africa reported the lowest and achieved the highest BR scores. The analysis reveals a strong negative correlation between data missing rates and BR performance scores, indicating that improved reporting can enhance the visibility of positive policy outcomes. However, high-quality data alone is not sufficient—outcomes also depend on effective policy design and implementation. The review process uncovered persistent data quality challenges, particularly the presence of extreme outlier values that undermine the reliability and comparability of reported results. These anomalies—such as implausible agricultural growth rates or disproportionate reductions in poverty—highlight weaknesses in data validation and signal a need for strengthened national data governance. The brief recommends institutionalizing the BR process, creating Kampala commitment specific data clusters, and investing in capacity building to improve data consistency and utilization. Strengthening national data systems is essential to achieving the poverty reduction goals of the Kampala Declaration.